Czech Republic : Technical Note on Selected Issues on the Credit Union Sector. (IMF Staff Country Reports; Country Report ;, 2012)
This technical note focuses on selected issues on the credit union (CU) sector in the Czech Republic. The business models of CUs in the Czech Republic are fundamentally different from traditional CUs that are typically non-for-profit cooperatives operated for the benefit of a defined set of members. The paper highlights that there is a need to restructure the CU sector, aimed at striking a delicate balance between minimizing financial and supervisory risks arising from the sector while recognizing the social role of prudently managed CUs.